Farr's physics for medical imaging - Yucel-Finn, Alim; McKiddie, Fergus; Prescott, Sarah; Bentley, Rachel; Allisy-Roberts, Penelope ([Amsterdam, Netherlands] : Elsevier, 2024)
"Written by topic experts, this new edition of Farr's Physics for Medical Imaging is designed specifically for trainee radiologists preparing for the physics component of their FRCR exams. The book effectively explains the principles and techniques behind the most common forms of medical imaging, including X-ray, CT, ultrasound, MRI, nuclear medicine, and fluoroscopy. Trainee radiologists and radiographers will find this an easy to understand and useful adjunct to their exam preparation - even those who haven't studied physics since school." --
Previous edition: published as by Penelope Allisy-Roberts, Jerry Williams. Edinburgh: Saunders, 2008
Place of publication from publisher's website
Includes bibliographical references and index
Keywords: Diagnostic imaging.http://id.loc.gov/authorities/subjects/sh85037507; Medical radiology.http://id.loc.gov/authorities/subjects/sh85110777; Medical physics.http://id.loc.gov/authorities/subjects/sh85083001; Diagnostic Imaging.(DNLM)D003952.https://id.nlm.nih.gov/mesh/D003952; Physics.(DNLM)D010825.https://id.nlm.nih.gov/mesh/D010825